1996
DOI: 10.1111/j.1699-0463.1996.tb00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of systemic mycoses by specific immunohistochemical tests

Abstract: of systemic mycoses by specific immunohistochemical tests. APMIS 104, 241-258, 1996. Immunohistochemistry has proved to be a powerful tool for the accurate diagnosis of a number of important mycoses in humans and animals, such as aspergillosis, candidosis, cryptococcosis, blastomycosis, coccidioidomycosis, histoplasmosis capsulati and duboisii, paracoccidioidomycosis, fusariosis, pseudallescheriosis (scedosporiosis), sporotrichosis, trichosporonosis, penicilliosis, and zygomycosis (mucormycosis). These tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 71 publications
3
70
0
7
Order By: Relevance
“…Situação semelhante tem sido descrita por outros autores em infecções micóticas que, muitas vezes, não apresentam alterações clínicas características que permitam um diagnóstico presuntivo (Kaufman 1992, Jensen et al 1996, seguido da ausência de cultura micológica, que é a técnica padrão-ouro (Lima et al 1977), e que permite a identificação definitiva do agente etiológico. Consequentemente, o agente causal de doenças micóticas (e oomicóticas) pode ser encontrado ou suspeitado somente durante o exame histopatológico dos tecidos afetados (Jensen et al 1996). Nesses casos, nos quais não é possível a cultura e a identificação do fungo, o reconhecimento das características morfológicas e histoquímicas das leveduras de Cryptococcus spp.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Situação semelhante tem sido descrita por outros autores em infecções micóticas que, muitas vezes, não apresentam alterações clínicas características que permitam um diagnóstico presuntivo (Kaufman 1992, Jensen et al 1996, seguido da ausência de cultura micológica, que é a técnica padrão-ouro (Lima et al 1977), e que permite a identificação definitiva do agente etiológico. Consequentemente, o agente causal de doenças micóticas (e oomicóticas) pode ser encontrado ou suspeitado somente durante o exame histopatológico dos tecidos afetados (Jensen et al 1996). Nesses casos, nos quais não é possível a cultura e a identificação do fungo, o reconhecimento das características morfológicas e histoquímicas das leveduras de Cryptococcus spp.…”
Section: Discussionunclassified
“…Infecções micóticas muitas vezes não apresentam alterações clínicas e lesões macroscópicas características que permitam um diagnóstico presuntivo (Kaufman 1992, Jensen et al 1996, o qual possa ser confirmado pela cultura micológica, que é a técnica padrão-ouro (Lima et al 1977). Consequentemente, o agente causal pode ser encontrado ou suspeitado somente durante o exame histopatológico dos tecidos afetados (Jensen et al 1996).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Unfortunately, many of the filamentous fungi cannot be reliably differentiated from one another with any of the routine fungal stains (Phillips and Weiner, 1987;Buckley et al, 1992;Reed et al, 1993;Jensen et al, 1993;Jensen et al, 1996a;Fenelon et al, 1999), because the appearance of fungi in sections is affected by steric orientation, age of the fungi, type of infected tissue, the number of fungal elements present, and the host response Jensen, 1994). It has also been reported that sometimes, and most often in chronic lesions containing non-viable hyphae, staining may only be weak, or in overstained sections fungal fragments may be masked.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some inflammatory reactions may suggest the possibility of a mycotic infection, even though no fungus is identified in tissue sections (Jensen, 1994;Jensen et al, 1996a). For these reasons, immunohistochemical techniques are increasingly used for obtaining specific diagnosis in cases of mycosis in birds (Carrasco et al, 1993;Jensen et al, 1997) as well as in mammals.…”
mentioning
confidence: 99%